2021
DOI: 10.1142/s0217984921501530
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic control cycle speed limit strategy for balanced reduction of travel time and emissions

Abstract: The vehicle exhaust has been one of the major sources of greenhouse gas emissions. With an increase in traffic volume, it has been found that the introduced intelligent traffic control is necessary. This paper investigated a novel VSL strategy considering the dynamic control cycle to improve the traffic efficiency and environmental benefit on freeway. An extension of the cell transmission model (CTM) was used to depict the traffic characteristics under VSL control, and integrated with the microscopic emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Experimental studies have shown that VSL and ramp metering are individually effective in alleviating traffic bottleneck congestion [24] but combining them can yield even greater benefits. Ma et al use a macroscopic micro emission model, using variable speed limits to coordinate and improve traffic efficiency and reduce exhaust emissions [25].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown that VSL and ramp metering are individually effective in alleviating traffic bottleneck congestion [24] but combining them can yield even greater benefits. Ma et al use a macroscopic micro emission model, using variable speed limits to coordinate and improve traffic efficiency and reduce exhaust emissions [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, given various practical limitations, these solutions are not applicable in all areas. Variable speed limits (VSL) are an important way to deal with traffic congestion and they are used widely in the field of transportation ( 1 , 2 ). Based on sensors and monitoring equipment, VSL systems provide real-time traffic data on the road, which can be integrated with emergency handling systems.…”
mentioning
confidence: 99%